(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article presents to reveal of features of English and Uzbek cultures bu making comparison each culture of national traditions. During the report,some hypothesises are examined with beneficial examples which can assist to identify differences and similarities: 1) to find national traditions which prevail in both English and Uzbek cultures ;2)what kind of similarities and differences we can find in Uzbek and English translations;3)nature, history, climate, geographical locations of these countries can effect to culture and traditions;4) folk traditions are needed to better comprehense the English and Uzbek languages;5) flattering is used in both destinations ;6) family values.